The effect of training the health care providers with simulation model on the care of patients with chronic tracheostomy - Uyan, Zeynep Seda; Atağ, Emine; Ergenekon, Almala Pınar; Gökdemir, Yasemin; Gökler, Ozan; Ay, Pınar; Baş İkizoğlu, Nilay; Cenk, Mürüvvet; Erdem Eralp, Ela; Sivrikaya, Ulufer; Girit, Saniye; Çakır, Erkan; et al. (European Respiratory Society Journals Ltd, 2021)
Introduction: Tracheostomy care in children may be challenging, due to lack of knowledge of health care providers. The aim of this study was to determine the level of knowledge of health care providers who follow patients with tracheostomy and to increase this level with theoretical education and training in a simulation laboratory. Materials and Methods: Volunteer participants were subjected to a theoretical pretest which evaluated their knowledge level for the care, follow-up and treatment of patients with tracheostomy. Then, practical testing with three subheadings evaluating the change of the tracheostomy cannula was applied. After theoretical training and one-on-one practical training given to the participants with a simulation model, theoretical and practical posttests were applied. Results: Fifty-one health care providers from six tertiary pediatric clinics in Istanbul were enrolled in the educational course. Only 6 (11.8%) of them received standardised training programme previously. Regarding the theoretical tests, seven of the 33 questions were indicated as crucial. The knowledge level of the participants based on the crucial questions significantly increased after the training (p value <0.05 for all of the crucial questions). Total number of correct answers and correct answers of 3 subheadings also significantly increased after the practical training (p value <0.001 for all). Ninety-five percent of the participants assessed the course as good or excellent. Conclusion: Training in simulation laboratory together with theoratical education can improve the knowledge and skills of the health care providers enabling improved care of children with tracheostomy.
Keywords: Chronic Tracheostomy; Simulation Model; Health Care Providers